2021
DOI: 10.1080/13510002.2021.1907518
|View full text |Cite
|
Sign up to set email alerts
|

Zingerone (4-(four-hydroxy-3-methylphenyl) butane-two-1) modulates adjuvant-induced rheumatoid arthritis by regulating inflammatory cytokines and antioxidants

Abstract: Kazi (2021) Zingerone (4-(four-hydroxy-3-methylphenyl) butane-two-1) modulates adjuvant-induced rheumatoid arthritis by regulating inflammatory cytokines and antioxidants,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…Similarly, ZIN attenuated vancomycin-induced hepatotoxicity in rats with the same mechanism [40]. ZIN also showed the antioxidant and anti-inflammatory effects in multiple disease models [41][42][43]. Nevertheless, this is the first study reporting the positive role of ZIN on the polymicrobial sepsis model.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, ZIN attenuated vancomycin-induced hepatotoxicity in rats with the same mechanism [40]. ZIN also showed the antioxidant and anti-inflammatory effects in multiple disease models [41][42][43]. Nevertheless, this is the first study reporting the positive role of ZIN on the polymicrobial sepsis model.…”
Section: Discussionmentioning
confidence: 74%
“…A recent document explained that oral administration of zingerone, an active constituent of ginger (25 mg/kg, 3 weeks), to adjuvant-induced RA rats considerably decreased the amounts of NF-κB, transforming growth factor-beta (TGF-β), TNF-α, IL-1β, IL-6, and high-sensitivity C-reactive protein (hs-CRP), and significantly enhanced IL-10 levels. Moreover, zingerone restored the amounts of antioxidant enzymes [50]. Cedrol, a ginger active component, has been shown to improves RA by decreasing inflammation and preventing Janus kinase 3 (JAK3) phosphorylation [51].…”
Section: Zingiber Officinale (Ginger)mentioning
confidence: 99%
“…[24][25][26] In addition, some scholars have found that turmeric contained in Shengjiang (Rhizoma Zingiberis Recens) has good antioxidant and anti-inflammatory effects, and has a certain effect on the prevention and treatment of arthritis-related diseases. 27…”
Section: Shengjiang (Rhizoma Zingiberis Recens)mentioning
confidence: 99%